Book of Abstracts and Proceedings of the International Conference MODERN TRENDS IN BUSINESS, HOSPITALITY AND TOURISM , May, 13th‐14th 2021, Cluj‐Napoca - GAVRILETEA, Marius Dan; COROȘ, Monica-Maria (Presa Universitară Clujeană, 2021)
Abstract: The COVID-19 pandemic was first detected in December 2019 in Wuhan, China, and then spread rapidly to the rest of the world. The pandemic negatively affected all the economies in the world and great fluctuations were experienced in the global stock markets. This study investigated the impact of 2019 novel coronavirus on stress in the US financial markets during the period March 9, 2020-February 19, 2021 employing Bayer and Hanck (2013) cointegration analysis. The analyses revealed a negative impact of the COVID-19 pandemic on the financial market stress in the US in the short and long run.